2003
DOI: 10.1001/jama.289.23.3106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treating Depression and Low Perceived Social Support on Clinical Events After Myocardial Infarction

Abstract: Writing Committee for the ENRICHD Investigators C ARDIOVASCULAR DISEASE IS THE leading cause of death and a major cause of morbidity and disability in the United States, with an estimated 6 million people having symptomatic coronary heart disease (CHD). 1 Recent studies 2-7 have shown that depression and low perceived social support (LPSS) are associated with increased cardiac morbidity and mortality in CHD patients. In patients with CHD, the prevalence of major depression is nearly 20% and the prevalence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
370
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,625 publications
(378 citation statements)
references
References 70 publications
5
370
2
1
Order By: Relevance
“…Detrimental effects of living alone or reduced perceived social support on outcomes after MI have been reported 18. However, dynamic shifts in social network structure and composition are not reported in the cardiovascular literature, and psychosocial interventions after MI have failed to improve outcomes 19. Therefore, stroke may have a particular effect on sociality that makes patients more vulnerable to social network shrinkage, isolation, and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Detrimental effects of living alone or reduced perceived social support on outcomes after MI have been reported 18. However, dynamic shifts in social network structure and composition are not reported in the cardiovascular literature, and psychosocial interventions after MI have failed to improve outcomes 19. Therefore, stroke may have a particular effect on sociality that makes patients more vulnerable to social network shrinkage, isolation, and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study to date is the Enhancing Recovery in Coronary Heart Disease Patients (ENRICHD). 63 In this study, 2861 patients who had had a myocardial infarction and who had depression or low perceived social support were treated with cognitive behavioral therapy. The aim of the intervention was to "strengthen network ties to be more functional, supportive, and satisfying."…”
Section: Social Supportmentioning
confidence: 99%
“…Although at present there is no evidence that depression treatment offsets the risk of cardiovascular events, 63,201,202 a 2008 American Heart Association science advisory on depression and coronary heart disease, endorsed by the American Psychiatric Association, 203 recommended a specific stepped screening approach to identify patients who may require further assessment and treatment for depression. In an effort to best understand the impact of depression, the symptoms of which are complex, current studies are examining specific depression subtypes that most closely relate to distinct biological underpinnings.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Unfortunately, depression is often recurrent in patients with coronary artery disease 24 and, without treatment, is likely to persist. Studies have shown that cognitive behavioral therapy may reduce depressive symptoms, 36 and antidepressants may improve cardiac outcomes, as suggested by a post hoc analysis of the Enhancing Recovery in Coronary Heart Disease Patients trial. 37 The possible benefits of treating depression provide an opportunity to reduce adverse cardiovascular outcomes and their associated costs in this population.…”
Section: Discussionmentioning
confidence: 99%